2021
DOI: 10.31849/elsya.v4i1.6376
|View full text |Cite
|
Sign up to set email alerts
|

Politeness in Thesis Consultation by WhatsApp: Do Lecturers and Students Apply Different Strategies?

Abstract: The study of politeness in education setting interaction has increased in last decades. However, the investigation of politeness strategies in lecturer-student interaction using WhatsApp is relatively unexplored. Therefore, this study aims to explore politeness strategies used by a lecturer and students in virtual communication using WhatsApp during thesis consultation.  The researcher applied a mixed method: qualitative and quantitative research to discover the politeness phenomena in WhatsApp interaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The result of this study confirms that the lecturer used the bald on record strategy more frequently than students. This is in line with the results of research conducted by Pasaribu et al (2021) who found that lecturers are sometimes higher than students 109The Journal of English Literacy Education, Vol. 9, No.01, May 2022, pp.101-114 P-ISSN 2355-7486, E-ISSN 2621 in terms of affirmative expressions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The result of this study confirms that the lecturer used the bald on record strategy more frequently than students. This is in line with the results of research conducted by Pasaribu et al (2021) who found that lecturers are sometimes higher than students 109The Journal of English Literacy Education, Vol. 9, No.01, May 2022, pp.101-114 P-ISSN 2355-7486, E-ISSN 2621 in terms of affirmative expressions.…”
Section: Discussionsupporting
confidence: 89%
“…9, No.01, May 2022, pp.101-114 P-ISSN 2355-7486, E-ISSN 2621 in terms of affirmative expressions. They also utilize politeness strategies to make students feel satisfied reconsidering students' thesis (Pasaribu et al, 2021). It can be proven that all politeness strategies are used by both lecturers and students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, teachers have more power and have higher status than the students (Khusnia, 2017), and they perform so by using imperatives. Lastly, teachers used off-record strategy to maintain students' negative face by allowing students to interpret several meanings from their utterances which are rather vague or ambiguous (Pasaribu, Saragih, & Gea, 2021). In addition, compared to other strategies employed, politeness strategies were frequently used by the teachers, which is consistent with the result of the study of Rahayunigsih et al (2020).…”
Section: Discussionsupporting
confidence: 79%
“…Further, negative politeness strategies are what is often used to consider age difference, institutional postion, power, and social distance which is evident in the case of teacher and students in the classroom (Fitriyani and Andriyanti, 2020). Thirdly, bald-on record strategy, although the teachers did not try to minimize face threats to the students' face, it is considered as polite as this strategy works if the speaker has more power and position than the hearer in the situation (Pasaribu, Saragih & Gea, 2021). In this case, teachers have more power and have higher status than the students (Khusnia, 2017), and they perform so by using imperatives.…”
Section: Discussionmentioning
confidence: 99%